The effect of continuous geomagnetic storms on enhancements of ultrarelativistic electrons in the Earth’s outer radiation belt - Chen, Jingrun; Tang, Chaoling; Chu, Xinxin (Frontiers in Astronomy and Space Sciences, 2024)
Using the data of the Van Allen Probes, we study the evolutions of ultrarelativistic electrons (Ek > 3 MeV) in the Earth's outer radiation belt during the three continuous geomagnetic storm events. These continuous geomagnetic storm events include the two geomagnetic storms. During the recovery phase of the first geomagnetic storm, enhanced relativistic and ultrarelativistic electrons with lower energies (≥3.4 MeV) are observed. These enhanced relativistic electrons could be the source of ultrarelativistic electrons and contribute to ultrarelativistic electron acceleration during the second geomagnetic storm. While 3.4 MeV electrons could be further enhanced during the second geomagnetic storm. During the recovery phase of the second small or moderate geomagnetic storm, ultrarelativistic electrons with higher cutoff energies (≥5.2 MeV) and higher fluxes are observed. Compared to an isolated geomagnetic storm with similar solar wind and geomagnetic conditions, ultrarelativistic electrons with higher cutoff energies and higher fluxes are observed during the recovery phase of the second geomagnetic storm. We also find that continuous geomagnetic storm events may contribute even more to enhancements of ultrarelativistic electrons in the outer radiation belt if the second geomagnetic storm is a small or moderate storm with a low solar wind dynamic pressure and short-duration main phase. These can help us to further understand the evolutions of ultrarelativistic electrons in the Earth's outer radiation belt during geomagnetic storms.